Iatrogenic Iron Promotes Neurodegeneration and Activates Self-Protection of Neural Cells against Exogenous Iron Attacks. Issue 2 (12th January 2021) - Xia, Maosheng; Liang, Shanshan; Li, Shuai; Ji, Ming; Chen, Beina; Zhang, Manman; Dong, Chengyi; Chen, Binjie; Gong, Wenliang; Wen, Gehua; Zhan, Xiaoni; Zhang, Dianjun; et al.
Abstract: Metal implants are used worldwide, with millions of nails, plates, and fixtures grafted during orthopedic surgeries. Iron is the most common element of these metal implants. As time passes, implants can be corroded and iron can be released. Ionized iron permeates the surrounding tissues and enters circulation; importantly, iron ions pass through the blood–brain barrier. Can iron from implants represent a risk factor for neurological diseases? This remains an unanswered question. In this study, we discovered that patients with metal implants delivered through orthopedic surgeries have higher incidence of Parkinson's disease or ischemic stroke compared to patients who underwent similar surgeries but did not have implants. Concentration of serum iron and ferritin was increased in subjects with metal implants. In experiments in vivo, we found that injection of iron dextran selectively decreased the presence of divalent metal transporter 1 (DMT1) in neurons through increasing the expression of Ndfip1, which degrades DMT1 and does not exist in glial cells. At the same time, excess of iron increased expression of DMT1 in astrocytes and microglial cells and triggered reactive astrogliosis and microgliosis. Facing the attack of excess iron, glial cells act as neuroprotectors to accumulate more extracellular iron by upregulating DMT1, whereas neurons limit iron uptake through increasing DMT1 degradation. Cerebral accumulation of iron in animals is associated with impaired cognition, locomotion, and mood. Excess iron from surgical implants thus can affect neural cells and may be regarded as a risk factor for neurodegeneration. Graphical Abstract: